The Impact of a Life Design Counselling Program on the Level of Vocational Self-Efficacy and Career Guidance Skills of Second-Year High School Students - Mnadla, Sofiene; Zoghlami, Wael; Zerai, Zaineb; Rayani, Hbib; Elloumi, Ali (Journal of Cultural Analysis and Social Change, 2026)
This research study measures the level of vocational self-efficacy of Tunisian second-year high school students as an indicator of their career guidance skills. This study also assesses the influence of academic, gender, and environmental var-iables on this level. To this end, a reduced version of the Career Choice Self-Efficacy Scale (CDSESSF) was initially ad-ministered to a population of 731 students to determine their level of professional self-efficacy. The same questionnaire was then reused to assess the effect of a life design counseling program on their sense of self-efficacy in career choice, the choice of a major, and career guidance skills in a sample of forty students. The main results showed that the level of self-efficacy in career choice is average and is not affected by the gender variable. However, it is strongly influenced by the environment (F = 10,90 / p ˂ 0,001) and the academic paths (F = 10,62 / P ˂ .001) of the high school students. The life design counseling program had a positive impact on the decision-making and orientation skills of the participants.